Learning About Alphabetics and Fluency: Examining the Effectiveness of a Blended Professional Development Program for Kenyan Teachers - Noah Battaglia; Eileen Wood; Alexandra Gottardo; Livison Chovu; Clifford Ghaa; Edwin Santhosh; Natasha Vogel; Anne Wade; Philip C. Abrami (Education Sciences, 2025)
This study examined the effectiveness of an 18-week online blended teacher professional development program for Kenyan in-service teachers. Also, teachers received instruction on the use of an evidence-based early literacy software program for children. The 94 teachers completed two professional development training modules (alphabetics and fluency) and four surveys (one before and one after each module). Surveys assessed teachers’ confidence and knowledge consistent with the primary elements of the TPACK model (i.e., content, pedagogy, technology). Knowledge gains were observed for fluency content, but not alphabetics content. Across the program, there were gains in pedagogical knowledge and teachers’ confidence. Given the importance of technology in the present study, additional analyses involving intersections of key elements with technology were examined. Outcomes supported the importance of technological pedagogy for the overarching integrated TPACK model. Overall, the TPD and accompanying course material provided some support for teachers who struggle with literacy instruction.